Rationale and protocol for the 7- and 8-year longitudinal assessments of eye health in a cohort of young adults in the Raine Study. Issue 3 (25th March 2020) - Lee, Samantha Sze-Yee; Lingham, Gareth; Yazar, Seyhan; Sanfilippo, Paul G; Charng, Jason; Chen, Fred K; Hewitt, Alex W; Ng, Fletcher; Hammond, Christopher; Straker, Leon M; Eastwood, Peter R; MacGregor, Stuart; et al.
Abstract : Introduction: Eye diseases and visual impairment more commonly affect elderly adults, thus, the majority of ophthalmic cohort studies have focused on older adults. Cohort studies on the ocular health of younger adults, on the other hand, have been few. The Raine Study is a longitudinal study that has been following a cohort since their birth in 1989–1991. As part of the 20-year follow-up of the Raine Study, participants underwent a comprehensive eye examination. As part of the 27- and 28-year follow-ups, eye assessments are being conducted and the data collected will be compared with those of the 20-year follow-up. This will provide an estimate of population incidence and updated prevalence of ocular conditions such as myopia and keratoconus, as well as longitudinal change in ocular parameters in young Australian adults. Additionally, the data will allow exploration of the environmental, health and genetic factors underlying inter-subject differential long-term ocular changes. Methods and analysis: Participants are being contacted via telephone, email and/or social media and invited to participate in the eye examination. At the 27-year follow-up, participants completed a follow-up eye screening, which assessed visual acuity, autorefraction, ocular biometry and ocular sun exposure. Currently, at the 28-year follow-up, a comprehensive eye examination is being conducted which, in addition to all the eye tests performed at the 27-year follow-up visit, includes tonometry, optical coherence tomography, funduscopy and anterior segment topography, among others. Outcome measures include the incidence of refractive error and pterygium, an updated prevalence of these conditions, and the 8-year change in ocular parameters. Ethics and dissemination: The Raine Study is registered in the Australian New Zealand Clinical Trials Registry. The Gen2 20-year, 27-year and 28-year follow-ups are approved by the Human Research Ethics Committee of the University of Western Australia. Findings resulting from the study will be published in health or medical journals and presented at conferences. Trial registration number: ACTRN12617001599369; Active, not recruiting.